Protecting Construction Worker Health and Safety in Ontario, Canada: Identifying a Union Safety Effect. Issue 12 (December 2015) - Amick, Benjamin C.; Hogg-Johnson, Sheilah; Latour-Villamil, Desiree; Saunders, Ron
Abstract : Objectives: Do Ontario unionized construction firms have lower workers' compensation claims rates compared with nonunion firms? Methods: Building trade and construction trade association lists of union contractors were linked to Workplace Safety and Insurance Board claims data for 2006 to 2012. Data were pooled for 2006 to 2012, and negative binomial regressions conducted with adjustment to estimate a union safety effect. Results: The sample included 5797 unionized and 38, 626 nonunion construction firms. Total claims rates were 13% higher (1.13, 1.09 to 1.18) in unionized firms because of higher allowed no-lost-time claim rates (1.28, 1.23 to 1.34), whereas the lost-time claims rate was 14% lower (0.86, 0.82 to 0.91). Conclusions: Unionized construction firms compared with nonunion firms have higher no-lost-time and lower lost-time claims rates. Unionized firms may encourage occupational injury reporting and reduce risks through training and hazard identification and control strategies. Abstract : Supplemental Digital Content is available in the text